2016
DOI: 10.1021/acs.iecr.5b04892
|View full text |Cite
|
Sign up to set email alerts
|

Semiempirical Model for the Solubility of Rare Earth Oxides in Molten Fluorides

Abstract: The importance of recycling and producing rare earth (RE) materials has been highlighted by the critical raw materials study in the European Union (EU). Oxide-fluoride electrolysis is one of the dominant technologies to produce rare earth metals (REMs) or alloys. The solubility of rare earth oxides (REOs) is one of the critical issues during this process. In this research, a model is developed to predict the REO solubility in molten fluorides, based on the systematic analysis of different influential factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 20 publications
3
37
0
1
Order By: Relevance
“…aThe solubility was obtained from ref (22), and the density of the melt was calculated according to the data from ref (9). …”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…aThe solubility was obtained from ref (22), and the density of the melt was calculated according to the data from ref (9). …”
Section: Results and Discussionmentioning
confidence: 99%
“…The previous research 22 shows that the relationship between solubility and temperature can be expressed aswhere x is a function related to the melt composition, and A is a positive constant in J/mol. For LiF-NdF 3 melt, 22 the Nd 2 O 3 solubility can be calculated via 22 where x i is the mole fraction of compound i in the original melt without dissolved Nd 2 O 3 .…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the solubility of REO in fluoride melts was widely researched [10][11][12][13][14][15][16][17][18][19][20][21]. It was found that the solubility was relatively low and the melts with high temperature and strong corrosiveness so that there were difficulties for accurate measuring the concentration of REO in fluoride melts.…”
Section: Introductionmentioning
confidence: 99%